Improving the signal-to-noise ratio in thermal flaw detectors by means of spectral filtering; The Soviet journal of nondestructive testing; Vol. 21, iss. 8 - Vavilov V. P. Vladimir Platonovich (1985, 1985)
By analyzing the operation of infrared devices that perform the function of thermal flaw detectors, relationships have been derived which make it possible to evaluate the signal-to-noise ratio in various spectral intervals.